STUDY OF ECONOMIC CLASS PASSENGER RATES FOR PEOPLE TRANSPORTATION TRAVEL IN NORTH KALIMANTAN PROVINCE - Bakri, Muhammad Djaya; Syarif, Iif Ahmad; Prihartanto, Eko; Hernadi, Ahmad (Universitas Ibn Khaldun Bogor, 2021)
Establishing North Kalimantan as the 34th province in Indonesia with the provincial capital located in Tanjung Selor, Bulungan Regency, has influenced the pattern of transportation used by society between regions. Previously, most people traveled to Tarakan city by sea transportation because Tarakan is an island city and has a strategic role regionally as a National Activity Center (PKN) in North Kalimantan. Since January 2020, the North Kalimantan Transportation Service has permitted public transportation routes to Perum DAMRI Tanjung Selor Branch to serve three round-trips (pp) routes, namely: Tanjung Selor-Malinau (TGS-MLN), Tanjung Selor-Tana Tidung (TJS-KTT), and Malinau-Salang (MLN-SLG). This study aims to find the ideal fare for public transportation for people on the route, taking into account the Vehicle Operating Cost (VOC), the ability and willingness to pay (ATP and WTP) of DAMRI Bus users, as well as the user's willingness to pay. Pay more or WTP from Contingency Valuation (WTP-CV) if you get better service during the trip. The current single-trip DAMRI Bus fare is IDR 150,000.00 for the TJS-MLN/MLN-TJS route, the TJS-KTT/KTT-TJS route is IDR 100,000.00, and for the MLN-SLG/SLG-MLN route of IDR 50,000.00. The results of the study based on the VOC obtained one-time trip rates for each route, respectively: IDR 135,633.21, IDR 119,046.86 and IDR 35,186.00. The respondents' ATP analysis results obtained a one-time trip fare for each route in a row: IDR 142,994.05, IDR 119.747.47 and IDR 63.750.00. Meanwhile, respondents' WTP was obtained for each route: IDR 110,519.48, IDR 94,545.45, and IDR 39,107.14. The respondents' WTP-CV values were also obtained on each route, amounting to IDR 14,675.32, IDR 11,409.09, and IDR 8,303.57. Considering the captive rider as an economy class passenger and the benefits of the DAMRI Bus operator, the proposed tariffs for each route are IDR 130,000, IDR 110,000, and IDR 48,000.